Dual-breakdown direct-current triboelectric nanogenerator with synergistically enhanced performance. (August 2022) - Li, Guang; Wu, Shuying; Sha, Zhao; Zhou, Yang; Wang, Chun-Hui; Peng, Shuhua
Abstract: Direct-current triboelectric nanogenerators (DC-TENGs) can directly convert mechanical energy to DC power without any rectifier and hence hold great potential as a lightweight and wearable energy harvesting technology. However, most of the recently reported DC-TENGs required metal frictional electrodes (FE-DC-TENGs) to achieve unidirectional charge flow, which limits the choices of materials for fabricating DC-TENGs and causes unwanted charge dissipation. Herein, we present a new strategy of constructing DC-TENGs with both tribo-materials being dielectrics while the close-loop of unidirectional charge flow is achieved by a dual-breakdown mechanism for the first time. The dual-breakdown DC-TENG (DB-DC-TENG) demonstrates greatly improved output performance compared with the FE-DC-TENGs, thanks to a synergistic effect between the two breakdown paths and the inhibition of tribo-charge wastage from unwanted breakdown in FE-DC-TENGs. The DB-DC-TENG has been shown to directly power electronic devices without any rectifier. To demonstrate the potential of the new DB-DC-TENG, it was placed in a backpack to harvest energy during walking/jogging. The findings of this work establish a new method for constructing high performance DC-TENGs using commonly available dielectric tribo-materials that can yield synergy between two simultaneous air breakdowns to significantly boost the energy harvesting efficiency. Graphical Abstract: ga1 Highlights: DB-DC-TENG uses commonly available dielectric materials as both tribo-layers. Dual breakdown paths are rationally introduced to replace metal frictional electrodes. DC output reaching 600 V, 1666 μA m −2 and 1.85 μC per cycle with constant current source characteristic. Improved performance of DB-DC-TENG by avoiding unwanted breakdown and introducing synergistic effect.